Advances in building information modeling : First Eurasian BIM Forum, EBF 2019, Istanbul, Turkey, May 31, 2019, Revised Selected Papers /: First Eurasian BIM Forum, EBF 2019, Istanbul, Turkey, May 31, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available